A cobalt–manganese layered oxide/graphene composite as an outstanding oxygen evolution reaction electrocatalyst. Issue 72 (23rd August 2021) - Kobayashi, Hiroaki; Sugawara, Yuuki; Yamaguchi, Takeo; Honma, Itaru
Abstract : A one-pot synthesis for graphene-deposited layered-type cobalt–manganese oxide remarkably enhanced its OER mass activity in alkaline water splitting. Abstract : To enhance the oxygen evolution reaction mass activity of cobalt–manganese layered oxide (CMO), we develop a one-pot synthetic process to anchor CMO onto graphene sheets (CMO/G). Its mass activity is 66-fold higher than that of physically mixed bare CMO with graphene and even better than those of previously reported graphene-supported first-row transition metal oxide-based electrocatalysts. The remarkable mass activity is attributed to the excellent intrinsic activity of CMO, small and well-dispersed CMO nanosheets on graphene sheets and hydrophilized graphene due to the synthetic process. Furthermore, CMO/G exhibits excellent stability.